Prescriptive analytics : the final frontier for evidence-based management and optimal decision making - Delen, Dursun (Pearson Education, 2019)
Prescriptive analytics is more directly linked to successful decision-making than any other form of business analytics. It can help you systematically sort through your choices to optimise decisions, respond to new opportunities and risks with precision, and continually reflect new information into your decisioning process. In Prescriptive Analytics, analytics expert Dr. Dursun Delen illuminates the field's state-of-the-art methods, offering holistic insight for both professionals and students. Delen's end-to-end, all-inclusive approach covers optimisation, simulation, multi-criteria decision-